Solar-Powered Automatic Water Pump for Energy Independence in Taruna Tani Sukamandiri Farmers’ Group - Nurdiansyah, Rian; Ruslan, Januar Arifin; Hamdani, Yuda Muhammad (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service program was conducted in 2025 with the Taruna Tani Sukamandiri Farmers’ Group in Ciamis Regency to address water scarcity and high fuel dependency in rainfed farming. An automatic solar-powered water pump system was introduced to strengthen energy independence, reduce irrigation costs, and increase the productivity of chili and cucumber crops. The program was implemented through five stages: coordination, technology installation, training, mentoring and evaluation, and ensuring sustainability. Results showed a significant reduction in diesel pump usage, cutting operational costs by IDR 1–1.5 million per season. Irrigation efficiency improved crop yields during the first two harvests, although the third harvest declined due to excessive rainfall. Farmers actively participated in installation, training, and maintenance, while students gained valuable hands-on learning. Academic outputs include a submitted journal article and a draft technical manual being processed for intellectual property rights, making this program a replicable model of sustainable agriculture.